Vaccine Science and Immunization Guideline : A Practical Guide for Primary Care - Rockwell, DO, Pamela G. (Springer International Publishing : Imprint: Springer, 2017)
This book is a comprehensive resource on vaccines and immunizations for primary care physicians, advanced practice providers, and trainees. We are now seeing a rise in measles and the potential for rises in other previously rare infectious diseases, significantly due to public and physician misconceptions and misinformation about vaccines. The text addresses this issue by consolidating historical and current advances in vaccine science from how vaccines are developed to CDC recommendations on how and when to administer them. Expert authors also address barriers to improving vaccination rates in the U.S. and offer evidence-based recommendations on overcoming those barriers. This is an essential guide for primary care physicians, family physicians, pediatricians, internists, residents, medical students, mid-level providers, and learners for understanding vaccines and improving preventative care for their patients.
Keywords: Medicine.; General practice (Medicine).; Public health.; Internal medicine.; Pediatrics.; Primary care (Medicine).; elektronické knihy; electronic books